Bust of a deity flanked by two celestial beings on the lower chaitya arch - Temples of India Project Team (Jio Institute, 2024)
The side walls of the garbhagriha have windows that are topped by double chaitya arches. The lower chaitya arch depicts the bust of a deity flanked by two celestial beings. The upper chaitya arch shows a grassamukha.